2001
DOI: 10.1128/mcb.21.16.5299-5305.2001
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signals Induce the Expression of c-FLIP

Abstract: Members of the tumor necrosis factor (TNF) receptor family and their corresponding ligands are critical regulators of apoptosis and various other cellular processes. Some of the receptors (Fas, TNF-R1, TRAIL-R1, TRAIL-R2, TRAMP/ DR3, DR6, and EDA-R) contain a cytoplasmic region, called the death domain (DD), which is essential for cell death signaling (18,22). Signals emanating from Fas and TNF-R1 have been intensively studied (14). Upon receptor activation, the DD of Fas undergoes direct homotypic interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
631
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 764 publications
(666 citation statements)
references
References 31 publications
24
631
3
2
Order By: Relevance
“…Interestingly, whereas LTC are in most respects similar to freshly activated T cells -both are CD95 type II in terms of DISC formation, show similar DISC activity and similar expression levels of anti-apoptotic Bcl-2 family members, they differ markedly with respect to c-FLIP expression. Freshly activated T cells express elevated levels of c-FLIP, especially its short splice variant c-FLIP S [38], possibly a direct effect of TCR signaling and activation of the NF-jB pathway [42,43]. In contrast, we did not detect elevated levels of c-FLIP in LTC consistent with the absence of recent TCR stimulation.…”
Section: Discussioncontrasting
confidence: 69%
“…Interestingly, whereas LTC are in most respects similar to freshly activated T cells -both are CD95 type II in terms of DISC formation, show similar DISC activity and similar expression levels of anti-apoptotic Bcl-2 family members, they differ markedly with respect to c-FLIP expression. Freshly activated T cells express elevated levels of c-FLIP, especially its short splice variant c-FLIP S [38], possibly a direct effect of TCR signaling and activation of the NF-jB pathway [42,43]. In contrast, we did not detect elevated levels of c-FLIP in LTC consistent with the absence of recent TCR stimulation.…”
Section: Discussioncontrasting
confidence: 69%
“…In this model, consistent with previous reports, there is no effect of necrostatin on caspase activity (Degterev et al, 2005), and in necrostatin-treated mice, there is an increase in the number of cells with an apoptotic profile. The decrease in FLIP gene and protein expression in necrostatin-treated mice may also support increased apoptosis (Kreuz et al, 2001) because FLIP normally acts as a dominant negative for caspase 8 (Micheau et al, 2001). The shift to a greater incidence of apoptosis in necrostatin-treated mice after HI is consistent with these findings.…”
Section: Discussionsupporting
confidence: 68%
“…Recent work has uncovered that A20 promotes the elimination of RIP1 in the TNF-R1 complex by replacing K63 ubiquitin chains with K48 polyubiquitin, thereby acting as both a deubiquitinating enzyme and as an E3 ligase to downregulate NF-kB signaling to suppress chronic inflammation and cell death . cFLIP potently suppresses death receptor-induced apoptosis, as it blunts activation of pro-caspase-8 and -10 (Micheau et al, 2001;Kreuz et al, 2004). It has recently been shown that cFLIP also participates along with caspase-8 in promoting NF-kB activation via BCL-10, mucosa-associated-lymphoidtissue lymphoma-translocation gene 1 (MALT1) and RIP1 and thus plays a key role in T-cell survival and proliferation following T-cell-receptor stimulation (Abraham and Shaham, 2004;Zhou et al, 2004;Launay et al, 2005, reviewed in Budd et al, 2006.…”
Section: Suppression Of Apoptosis and Necrosismentioning
confidence: 99%